Hydrophobic hydrogen bond enhanced hydrogel and preparation method thereof

Through the synergistic effect of specific hydrophilic and hydrophobic monomers, combined with multifunctional group crosslinking agent and redox initiation system, a stable three-dimensional network structure is constructed, which solves the shortcomings of existing hydrogel materials in terms of mechanical properties and temperature and humidity resistance, and achieves high-strength, high elasticity and good stability of hydrophobic hydrogen bond-enhanced hydrogels, suitable for diverse application scenarios.

CN119591807AActive Publication Date: 2025-03-11HEBEI UNIV OF ENG
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411938324.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing hydrogel materials have shortcomings in mechanical properties, temperature and humidity resistance and preparation processes, and are difficult to meet diversified needs, especially in applications in high mechanical properties and high temperature and high humidity environments.

Method used

Specific hydrophilic monomers and hydrophobic monomers are used to form abundant hydrogen bonds and hydrophobic interactions, combine multifunctional crosslinking agents and redox initiation systems to construct a stable three-dimensional network structure, and prepare a high-strength, high elasticity and good stability of hydrophobic hydrogen bond-enhanced hydrogel.

Benefits of technology

It significantly improves the tensile strength and elongation of breaking of the hydrogel, enhances its structural integrity and stability in high temperature and high humidity environments, and the flexible preparation process enables it to be optimized and customized according to different needs, and is suitable for a variety of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591807A_ABST
    Figure CN119591807A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer chemistry, in particular to hydrophobic hydrogen bond enhanced hydrogel and a preparation method thereof, and the hydrophobic hydrogen bond enhanced hydrogel is prepared from 30-60 parts of hydrophilic monomer, 10-30 parts of hydrophobic monomer, 1-5 parts of cross-linking agent, 0.1-1 part of initiator and 50-100 parts of water. The preparation method comprises the following steps: dissolving and stirring to obtain a mixed solution, heating and reacting to obtain a precursor, and soaking in water and drying to obtain the product. The material has the remarkable advantages that the mechanical property is excellent, the tensile strength is 1.2-2.2 MPa, the elongation at break is 750%-1250%, and the material is derived from unique monomer action and a cross-linked network; temperature and humidity resistance is good, the structure is good in 10 days under the humidity of 50 DEG C and 80%, and the loss rate is low; the preparation process is flexible, various parameters are adjustable, industrial production is facilitated, and the method has application prospects and development potential in multiple fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer chemistry, and in particular to a hydrophobic hydrogen bond enhanced hydrogel and a preparation method thereof. Background Art

[0002] As a material with unique properties, hydrogel has shown potential application value in many fields. However, existing hydrogel materials have many limitations in performance and preparation process, and it is difficult to meet the growing and diversified needs.

[0003] In terms of mechanical properties, the tensile strength of traditional hydrogels is generally low, usually difficult to reach 1MPa, and the elongation at break is often limited to about 300%. This is because its network structure is not stable enough and lacks effective interaction to enhance the mechanical properties of the material. For example, common hydrophilic monomers such as polyvinyl alcohol used in the past, although having certain hydrophilicity, cannot form abundant hydrogen bonds like the specific hydrophilic monomers in the present invention (polyol monomers containing carboxyl and hydroxyl groups, and the molar ratio of carboxyl and hydroxyl groups and the degree of polymerization have a specific range) when forming a hydrogel network, resulting in insufficient strength and elasticity of the hydrogel. At the same time, the hydrophobic components in traditional hydrogels are often improperly selected, and fail to form effective hydrophobic micro-regions to interact with the hydrophilic parts, making the overall network structure loose and unable to withstand large external force stretching. When used as a biomedical tissue engineering scaffold, it is difficult to reliably support cell growth and tissue repair, and is prone to rupture and damage, which seriously limits its application in fields with high requirements for mechanical properties.

[0004] Existing hydrogels perform poorly in terms of temperature and humidity resistance. When placed in a high temperature and high humidity environment, such as at 50°C and 80% humidity, the structural stability of traditional hydrogels will be greatly challenged. This is because its internal chemical bonds and intermolecular forces are weak, and it cannot effectively resist the erosion of water and the damage of thermal motion. The combination of its hydrophilic and hydrophobic components is unreasonable, and it does not form a structure of coordinated hydrophilic and hydrophobic monomers and a stable cross-linked network as in the present invention. As a result, after being placed in a high temperature and high humidity environment for a short period of time, problems such as loose structure and serious quality loss will occur. It cannot meet the use requirements in outdoor products in tropical areas, industrial sensors in high temperature and high humidity environments, and greatly reduces its scope of application.

[0005] From the perspective of preparation technology, the preparation technology of traditional hydrogels is relatively fixed and single. The range of raw material selection is limited, and key parameters such as the ratio of hydrophilic monomers and hydrophobic monomers, the amount of cross-linking agents and initiators are difficult to flexibly adjust according to actual needs. Reaction conditions such as temperature, time, and drying conditions also lack diverse choices. This makes the prepared hydrogels have relatively single properties and cannot meet the special requirements of hydrogel performance in different application scenarios. Moreover, traditional preparation processes may require more harsh conditions such as high temperature, which not only increases energy consumption, but may also have an adverse effect on the structure and properties of the monomers, resulting in unstable product quality. It is also not conducive to large-scale industrial production, and the production cost is high, which limits the widespread application and further development of hydrogel materials.

[0006] The Chinese invention patent with publication number CN110938168A discloses a hydrophobic hydrogen bond enhanced hydrogel and a preparation method thereof, but its elongation at break, tensile strength, and structural integrity in high temperature and high humidity environments have drawbacks and are difficult to meet the needs.

[0007] In summary, the existing hydrogel technology has obvious deficiencies in mechanical properties, temperature and humidity resistance, and preparation process. There is an urgent need for a new hydrogel material and its preparation method to overcome these problems in order to expand the application field of hydrogels and improve their performance and practicality. The present invention is proposed based on such a background. Summary of the invention

[0008] The object of the present invention is to provide a hydrophobic hydrogen bond enhanced hydrogel and a preparation method thereof to solve the problems raised in the above background technology.

[0009] In order to solve the above technical problems, the technical solution provided by the present invention is: a hydrophobic hydrogen bond enhanced hydrogel is prepared from the following raw materials in parts by weight:

[0010] 30-60 parts of a hydrophilic monomer, wherein the hydrophilic monomer is a polyol monomer containing carboxyl and hydroxyl groups, wherein the molar ratio of the carboxyl group to the hydroxyl group is 1:2-1:3, and the degree of polymerization of the hydrophilic monomer is 100-500. The hydrophilic monomer with this specific structure can form abundant hydrogen bonds in the hydrogel network, thereby enhancing the hydrophilicity and mechanical properties of the hydrogel;

[0011] 10-30 parts of a hydrophobic monomer, wherein the hydrophobic monomer is a long-chain alkyl acrylate monomer, and the alkyl chain length thereof is 8-16 carbon atoms. The hydrophobic monomer can form a hydrophobic microdomain in the hydrogel system, and interact with the hydrophilic monomer to further enhance the network structure and stability of the hydrogel through hydrophobic association;

[0012] 1-5 parts of a cross-linking agent, wherein the cross-linking agent is an aziridine compound with a multifunctional group, and its functionality is 3-6, which can efficiently cross-link with hydrophilic monomers and hydrophobic monomers during the hydrogel formation process to form a three-dimensional network structure, thereby improving the strength and elasticity of the hydrogel;

[0013] 0.1-1 part of initiator, wherein the initiator is a redox initiation system composed of persulfate and sulfite, and the molar ratio of the two is 1:0.5-1:1.5. The initiation system can initiate polymerization at room temperature, making the preparation process of the hydrogel more gentle and controllable, and avoiding the influence of high temperature on the structure and performance of the monomer;

[0014] 50-100 parts of water, wherein the water is deionized water, and is subjected to multi-stage reverse osmosis and ion exchange treatment to ensure that the impurity content in the water is less than 1 ppm, thereby avoiding the adverse effects of impurities on the performance of the hydrogel and ensuring the purity and stability of the hydrogel, thereby preparing a hydrophobic hydrogen bond-reinforced hydrogel with high strength, high elasticity and good stability.

[0015] Preferably, the hydrophilic monomer is a carboxyl polyethylene glycol hydroxyl monomer or a hydroxy-polyethylene glycol-carboxyl monomer.

[0016] Preferably, the hydrophobic monomer is octyl acrylate or hexadecyl acrylate.

[0017] Preferably, the crosslinking agent is a trifunctional aziridine crosslinking agent XT-630 or a hexafunctional aziridine crosslinking agent SR-633.

[0018] Preferably, the initiator is a potassium persulfate-sodium sulfite initiation system or an ammonium persulfate-sodium bisulfite initiation system.

[0019] A method for preparing a hydrophobic hydrogen bond enhanced hydrogel comprises the following steps:

[0020] Step 1: dissolving a hydrophilic monomer, a hydrophobic monomer, a crosslinking agent and an initiator in water, and stirring the mixture evenly under nitrogen protection to obtain a mixed solution;

[0021] Step 2: heating the mixed solution to 40-80°C and reacting for 2-8 hours to obtain a hydrogel precursor;

[0022] Step 3: Soak the hydrogel precursor in water for 12-48 hours and then dry it to obtain a hydrophobic hydrogen bond reinforced hydrogel.

[0023] As a preferred embodiment, the stirring time under nitrogen protection is 10-60 minutes.

[0024] As a preferred solution, the drying temperature is 40-60° C. and the drying time is 12-72 hours.

[0025] The advantages of the present invention are: the hydrophobic hydrogen bond enhanced hydrogel prepared by the present invention has excellent mechanical properties, and its tensile strength is between 1.2-2.2MPa, which is a great improvement over the existing technology. This is due to the hydrophobic interaction and hydrogen bond formed by specific hydrophilic monomers and hydrophobic monomers, combined with cross-linking agents to build a stable three-dimensional network. In the application of biomedical tissue engineering scaffolds, it can reliably support cell growth and tissue repair to avoid rupture and damage. The elongation at break is 750%-1250%, which is much higher than the 300% of the existing technology. The unique formula and process give the hydrogel good elasticity and plasticity. In the field of flexible electronic devices and wearable devices, it can adapt to complex deformation and improve stability and life.

[0026] The temperature and humidity resistance is good. After being placed in an environment of 50°C and 80% humidity for 10 days, the hydrogel structure of the present invention is complete and the mass loss rate is 1.8%-6.1%. However, the structure of the control sample is loose. This is due to the synergy of hydrophilic and hydrophobic monomers and the stability of the cross-linked network, which enables the hydrogel to resist moisture erosion and thermal motion damage. It has application potential in tropical outdoor products, high-temperature and high-humidity industrial sensors and other fields.

[0027] The preparation process of the present invention is flexible and controllable, and the ratio of hydrophilic and hydrophobic monomers, the amount of cross-linking agent initiator, reaction and drying conditions, etc. can be adjusted to produce a hydrogel with excellent performance. It can be optimized and customized as needed, which is in contrast to the fixed and simple process of the comparative example. It is conducive to industrial large-scale production, reduces costs, improves efficiency, and lays a foundation for the development of hydrogels with different properties. It has broad application prospects and development potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a bar graph comparing the tensile strength of Examples 1-5 and the comparative example.

[0029] Figure 2 It is a bar graph comparing the elongation at break of Examples 1-5 and the comparative example.

[0030] Figure 3 It is a bar graph comparing the mass loss rates of Examples 1-5 and the comparative example in a high temperature and high humidity environment. DETAILED DESCRIPTION

[0031] For the purpose of the following detailed description, it should be understood that the present invention may adopt various alternative changes and step sequences, unless expressly specified to the contrary. In addition, except in any operating examples, or otherwise indicated, all numbers representing the amount of ingredients used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the attached claims are approximate values ​​that vary according to the desired performance to be obtained by the present invention. At least it is not intended to limit the application of the doctrine of equivalents to the scope of the claims, and each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.

[0032] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0033] In addition, it should be understood that any numerical range described herein is intended to include all subranges subsumed therein. For example, a range of "1 to 10" is intended to include all subranges between (and including) the stated minimum value of 1 and the stated maximum value of 10, i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.

[0034] Embodiment 1:

[0035] Raw material formula: 45 parts of hydrophilic monomer (carboxyl polyethylene glycol hydroxyl monomer), 15 parts of hydrophobic monomer (octyl acrylate), 1 part of cross-linking agent (trifunctional aziridine cross-linking agent XT-630), 0.3 parts of initiator (potassium persulfate-sodium sulfite initiation system), and 50 parts of water.

[0036] Preparation process: Stir the above raw materials under nitrogen protection for 20 minutes to make them evenly mixed, then heat to 40°C and react for 4 hours to obtain a hydrogel precursor. After soaking the precursor in water for 24 hours, dry it at 45°C for 30 hours to obtain a hydrophobic hydrogen bond enhanced hydrogel.

[0037] Test results: The hydrogel has a tensile strength of 1.5 MPa and an elongation at break of 830%. After being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the structure is intact and the mass loss rate is 4.8%.

[0038] Embodiment 2:

[0039] Raw material formula: 60 parts of hydrophilic monomer (hydroxy-polyethylene glycol-carboxyl monomer), 20 parts of hydrophobic monomer (hexadecyl acrylate), 3 parts of cross-linking agent (hexafunctional aziridine cross-linking agent SR-633), 0.5 parts of initiator (ammonium persulfate-sodium bisulfite initiation system), and 70 parts of water.

[0040] Preparation process: Stir for 30 minutes under nitrogen protection, react at 80°C for 2 hours, soak in water for 12 hours, and dry at 50°C for 40 hours.

[0041] Test results: The tensile strength of the hydrogel reaches 1.8 MPa, the elongation at break is 920%, and the structure is intact after being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, with a mass loss rate of 3.9%.

[0042] Embodiment 3:

[0043] Raw material formula: 35 parts of hydrophilic monomer (carboxyl polyethylene glycol hydroxyl monomer), 10 parts of hydrophobic monomer (octyl acrylate), 5 parts of crosslinking agent (trifunctional aziridine crosslinking agent XT-630), 0.1 parts of initiator (potassium persulfate-sodium sulfite initiation system), and 55 parts of water.

[0044] Preparation process: nitrogen stirring for 10 minutes, reaction at 45°C for 8 hours, water soaking for 18 hours, and drying at 40°C for 20 hours.

[0045] Test results: The hydrogel has a tensile strength of 1.2 MPa and an elongation at break of 750%. After being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the structure is intact and the mass loss rate is 6.1%.

[0046] Embodiment 4:

[0047] Raw material formula: 30 parts of hydrophilic monomer (hydroxy-polyethylene glycol-carboxyl monomer), 25 parts of hydrophobic monomer (hexadecyl acrylate), 4 parts of cross-linking agent (hexafunctional aziridine cross-linking agent SR-633), 1 part of initiator (ammonium persulfate-sodium bisulfite initiation system), and 100 parts of water.

[0048] Preparation process: nitrogen stirring for 60 minutes, reaction at 70℃ for 6 hours, water soaking for 48 hours, and drying at 60℃ for 12 hours.

[0049] Test results: The hydrogel has a tensile strength of 2.0 MPa and an elongation at break of 1080%. After being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the structure is intact and the mass loss rate is 3.0%.

[0050] Embodiment 5:

[0051] Raw material formula: 55 parts of hydrophilic monomer (carboxyl polyethylene glycol hydroxyl monomer), 30 parts of hydrophobic monomer (octyl acrylate), 4.5 parts of crosslinking agent (trifunctional aziridine crosslinking agent XT-630), 0.9 parts of initiator (potassium persulfate-sodium sulfite initiation system), and 90 parts of water.

[0052] Preparation process: nitrogen stirring for 50 minutes, reaction at 75°C for 7 hours, water soaking for 42 hours, and drying at 60°C for 72 hours.

[0053] Test results: The hydrogel has a tensile strength of 2.2 MPa and an elongation at break of 1250%. After being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the structure is intact and the mass loss rate is 1.8%.

[0054] Comparative Example:

[0055] Raw material formula: 40 parts of ordinary hydrophilic monomer (polyvinyl alcohol, degree of polymerization 1700), 8 parts of hydrophobic monomer (ethyl butyrate), 3 parts of cross-linking agent (glutaraldehyde), 0.6 parts of initiator (ammonium persulfate), and 60 parts of ordinary distilled water.

[0056] Preparation process: Stir at room temperature for 10 minutes, react at 85℃ for 10 hours, and dry naturally.

[0057] Test results: The hydrogel has a tensile strength of 0.4 MPa and an elongation at break of 300%. After being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the structure becomes loose and cannot maintain its original shape, with a mass loss rate of 96%.

[0058] The test results of Examples 1-5 and Comparative Examples are shown in Table 1

[0059] Table 1

[0060]

[0061] With respect to the comparison between the above embodiments and the comparative examples, the specific advantages of the present invention are as follows:

[0062] Excellent mechanical properties: tensile strength: Figure 1 As shown, the tensile strength of the hydrogel prepared by the present invention is between 1.2-2.2MPa, while the comparative example is only 0.4MPa. This is due to the specific hydrophilic monomers (such as carboxyl polyethylene glycol hydroxyl monomers, hydroxy-polyethylene glycol-carboxyl monomers) and hydrophobic monomers (such as octyl acrylate, hexadecyl acrylate) selected by the present invention, which can form effective hydrophobic interactions and hydrogen bonds, and together with the cross-linking agent (such as trifunctional aziridine cross-linking agent XT-630, hexafunctional aziridine cross-linking agent SR-633), a stable and strong three-dimensional network structure is constructed, so that it can withstand greater external force stretching. In practical applications, for example, as a tissue engineering scaffold in the biomedical field, it can better support cell growth and tissue repair, is not prone to rupture and damage, and ensures safety and reliability of use.

[0063] Elongation at break: Figure 2As shown, the elongation at break of the hydrogel of the present invention is 750%-1250%, which is much higher than 300% of the comparative example. The high elongation at break indicates that the hydrogel has excellent flexibility and stretchability. This is because the unique raw material formula and preparation process of the present invention make the hydrogel network structure have good elasticity and plasticity, and can maintain structural integrity under a large degree of deformation. When used in the fields of flexible electronic devices, wearable devices, etc., this high flexibility can enable the hydrogel to better adapt to various complex deformation requirements and improve the stability and service life of the device.

[0064] Good temperature and humidity resistance: Figure 3 As shown, after being placed in a high temperature and high humidity environment of 50°C (humidity 80%) for 10 days, the hydrogel structures of Examples 1-5 are intact, with a mass loss rate of 1.8%-6.1%, while the comparative example has a loose structure and cannot maintain its original shape. This is due to the synergistic effect of the hydrophilic monomer and the hydrophobic monomer in the present invention and the stability of the cross-linked network, so that the internal hydrogen bonds and hydrophobic interactions of the hydrogel can effectively resist the erosion of water and the destruction of the structure by thermal motion under high temperature and high humidity conditions, thereby maintaining good physical properties and chemical stability. This temperature and humidity resistance makes the hydrogel have potential application value in fields such as outdoor products in tropical areas and industrial sensors in high temperature and high humidity environments, broadening its scope of application.

[0065] The preparation process is flexible and controllable: The embodiments of the present invention demonstrate a variety of raw material formulas and corresponding changes in preparation process parameters, such as the ratio of hydrophilic monomers and hydrophobic monomers, the amount of cross-linking agent and initiator, reaction temperature, time, stirring and drying conditions, etc., which can be adjusted within a certain range, and can prepare hydrogels with excellent performance. This shows that the preparation process of the present invention has strong flexibility and controllability, and can be optimized and customized according to actual production needs and product performance requirements. In contrast, the preparation process of the comparative example is relatively fixed and simple, lacks the ability to accurately control product performance, and is difficult to meet the needs of diverse application scenarios. This flexible and controllable preparation process is conducive to realizing industrial large-scale production, reducing production costs, and improving production efficiency. It also provides a basis for further research and development of hydrogel materials with different properties.

[0066] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A hydrophobic hydrogen bond enhanced hydrogel, characterized in that: It is prepared from the following raw materials in parts by weight: 30-60 parts of a hydrophilic monomer, wherein the hydrophilic monomer is a polyol monomer containing carboxyl and hydroxyl groups, wherein the molar ratio of the carboxyl group to the hydroxyl group is 1:2-1:3, and the degree of polymerization of the hydrophilic monomer is 100-500; 10-30 parts of a hydrophobic monomer, wherein the hydrophobic monomer is a long-chain alkyl acrylate monomer, and the length of the alkyl chain thereof is 8-16 carbon atoms; 1-5 parts of a cross-linking agent, wherein the cross-linking agent is an aziridine compound having a multifunctional group and a functionality of 3-6; 0.1-1 part of initiator, wherein the initiator is a redox initiation system consisting of persulfate and sulfite, and the molar ratio of the two is 1:0.5-1:1.5; 50-100 parts of water, wherein the water is deionized water, and has been processed by multi-stage reverse osmosis and ion exchange to ensure that the impurity content in the water is less than 1 ppm.

2. The hydrophobic hydrogen bond enhanced hydrogel according to claim 1, characterized in that: The hydrophilic monomer is a carboxyl polyethylene glycol hydroxyl monomer or a hydroxyl-polyethylene glycol-carboxyl monomer.

3. The hydrophobic hydrogen bond enhanced hydrogel according to claim 1, characterized in that: The hydrophobic monomer is octyl acrylate or hexadecyl acrylate.

4. The hydrophobic hydrogen bond enhanced hydrogel according to claim 1, characterized in that: The cross-linking agent is a trifunctional aziridine cross-linking agent XT-630 or a hexafunctional aziridine cross-linking agent SR-633.

5. The hydrophobic hydrogen bond enhanced hydrogel according to claim 1, characterized in that: The initiator is a potassium persulfate-sodium sulfite initiation system or an ammonium persulfate-sodium bisulfite initiation system.

6. A method for preparing a hydrophobic hydrogen bond enhanced hydrogel according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1: dissolving a hydrophilic monomer, a hydrophobic monomer, a crosslinking agent and an initiator in water, and stirring them evenly under nitrogen protection to obtain a mixed solution; Step 2: heating the mixed solution to 40-80°C and reacting for 2-8 hours to obtain a hydrogel precursor; Step 3: Soak the hydrogel precursor in water for 12-48 hours and then dry it to obtain a hydrophobic hydrogen bond reinforced hydrogel.

7. The preparation method according to claim 6, characterized in that: The stirring time under nitrogen protection is 10-60 minutes.

8. The preparation method according to claim 6, characterized in that: The drying temperature is 40-60° C. and the drying time is 12-72 hours.

Citation Information

Patent Citations

  • Hydrophobic hydrogen-bond-enhanced hydrogel and preparation method thereof

    CN110938168A

  • High-transparency, adhesive and self-healing hydrogel film and preparation method thereof

    CN114395071A

  • Self-healing and degradable polyethylene glycol-based epoxy elastomer as well as preparation method and application thereof

    CN114874415A

  • Fully-hydrophobic eutectic gel as well as preparation method and application thereof

    CN116375939A

  • Traditional Chinese medicine composition as well as preparation method and application thereof

    CN117414383A